Close coupling of plant functional types with soil microbial community composition drives soil carbon and nutrient cycling in tundra heath - Marianne Koranda (Centre for Microbiology and Environmental Systems Science, University of Vienna); Riikka Rinnan (Terrestrial Ecology Section, Department of Biology, University of Copenhagen); Anders Michelsen (Terrestrial Ecology Section, Department of Biology, University of Copenhagen) (Plant and Soil, 2023)
The abstract is available here: https://uscholar.univie.ac.at/o:1971478 The abstract is available here: https://uscholar.univie.ac.at/o:1971478